Identification and mutational analyses of KpsF gene containing PxIxIT motif in Aspergillus fumigatus - Yan Ma; Wenli Feng; Jiajuan Li; Wen Li; Ying Ji; Wen Cen (Journal of King Saud University: Science, 2020)
Invasive Aspergillosis (IA) has increased significantly in recent years in which about 90% is caused by Aspergillus fumigatus, and the mortality rate is on the rise. Its treatment has become a common problem clinically. Calcineurin (CaN) plays an important role in the morphogenesis and toxicity of Aspergillus fumigatus, making it an attractive antifungal target. Although the Calcineurin inhibitors FK506 and cyclosporine A have successfully applied in modern transplantation medicine, the systemic toxic and side effects of the two drugs have greatly limited their clinical antifungal applications. Previous studies have shown that CaN of the Aspergillus fumigatus is localized at the top and division of hyphae, and interactions of CaN with cbpA are closely related to the PxIxIT motif. The functioning of CaN is closely related to the PxIxIT motif. Calcineurin substrates or target proteins such as Crz1, SIm1, SIm2, Hph1, and CbpA all contain similar PxIxIT motifs, and similar motifs are present in the Aspergillus fumigatus KpsF gene sequence. We can find KpsF gene in the Aspergillus fumigatus genome through bioinformatics methods, which contains a similar motif in its sequence. Therefore, we can speculate that this motif may interact with Calcineurin, further illustrate the specific mechanism of pathogenesis of CaN in Aspergillus fumigatus, which will help us to have a deeper understanding of the pathogenesis of invasive aspergillosis and provide new ideas for us. By completing the construction of the Aspergillus fumigatus KpsF gene-deficient strain and over-exp strain, we found that the KpsF gene over-exp strain of Aspergillus fumigatus is significantly different from that of the control strain in morphology, and is different from the cbpA in calcium ion regulation. In the low concentration of Ca2+, KpsF may be involved in the negative feedback regulation of Calcineurin, and this negative feedback regulation is inhibited under the condition of high concentration Ca2+. Keywords: Aspergillus fumigatus, PxIxIT gene, KpsF gene, Calcineurin, Gene mutation